Strategy Wisata Cowindo Refreshing And Education Dalam Perspektif Promotion Mix Dan Community Based Tourism Di Desa Sendang Tulungagung - Setia, Nanda Permata; Askafi, Eka; Daroini, Ahsin (Universitas Islam Kadiri, 2025)
Marketing strategy is a marketing plan to support the company's operational activities so that the company's goals are achieved. The promotion strategy is also implemented by Wisata Cowindo Refreshing and Education in carrying out its operational activities. The strategy applied is the promotion mix cowindo tourism is tourism that implements community based tourism. The purpose of this research are 1) a researcher want to know about how the general description of Cowindo Tourism is Refreshing and Education 2) a researcher want to know about how the promotion mix strategy is applied to Cowindo Tourism Refreshing and Education based on Community Based Tourism 3) a researcher want to know about how the promotion mix strategy is for the development of Cowindo Tourism Refreshing and Education based on Community Based Tourism. This research is qualitative and it’s use a case study. The research data was get from observation, interview and documentation. The analysis of this research data used a hermeneutics. Checking the validity of the data uses two triangulations, technical triangulation and source triangulation. The location of the Cowindo Refreshing and Education Tour is in Pelem Hamlet, Sendang Village, Sendang District, Tulungagung Regency, East Java Province. It is about 40 minutes from the center of Tulungagung City. Cowindo Tourism applies a promotion mix strategy according to the theory of Philip Kotler & Gary Armstrong. According to Philip Kotler & Gary Armstrong (2004: 600-601) namely advertising, sales promotion, public relations and direct marketing.Community empowerment (local community) at the Cowindo Refreshing and Education Tourism site to become a tourist destination (destination) through tourism business activities is one of the development models that is currently getting a lot of attention from various groups and will become an important agenda in tourism development in the future